2014
DOI: 10.1016/j.suscom.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Green IT – Available data and guidelines for reducing energy consumption in IT systems

Abstract: Green IT has become one of the most discussed topics in the last new years. However, the related literature is dispersed and it is difficult to give precise definitions. Nowadays saving energy is an interesting and interdisciplinary key challenge. Hardware manufacturers and designers have usually handled the problem, in the field of IT, but recently software energy efficiency gathered the interest of industry and academic research. However, writing energy efficient software requires proper metrics to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…GIT is an efficient resource consumption that utilizes IT infrastructure as well as deployment managerial, human practices, and organizational policies towards reducing the negative effect of IT (Molla et al 2014). Numerous organizations have been recommended to have GIT on their agenda (Ardito and Morisio 2014), and fastened to their strategies (Hernandez and Ona 2016) to reach the full benefits of GIT.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…GIT is an efficient resource consumption that utilizes IT infrastructure as well as deployment managerial, human practices, and organizational policies towards reducing the negative effect of IT (Molla et al 2014). Numerous organizations have been recommended to have GIT on their agenda (Ardito and Morisio 2014), and fastened to their strategies (Hernandez and Ona 2016) to reach the full benefits of GIT.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Abbreviated versions of the final 36 statements are shown in Figures 2 to 7 and a complete copy is available online. 1 In addition, we asked free response follow up questions for areas of particular interest when the response to a question indicated the respondent may have insight or evidence to share. For example, if a respondent indicated that their applications have energy usage goals or requirements, we asked them to provide an example.…”
Section: Protocolmentioning
confidence: 99%
“…There is also research focused on both developing tools to help developers examine/improve the energy usage of their applications (e.g., [5,18,19,21,36,56]), and on models to support the green software development process [1,41]. Additional information about such existing work is provided in Section 5 where we discuss state-of-the-art green software engineering research in the context of our study's findings.…”
Section: Related Workmentioning
confidence: 99%
“…There are a number of studies on the general energy efficiency of data centres and their cooling alternatives in the literature [18][19][20][21][22][23][24][25]. Schmidt et al [26] looked into powering and cooling a modern centre via co-generation.…”
Section: Introductionmentioning
confidence: 99%